THE USE OF PISA RESEARCH IN ADDRESSING CHEMICAL PROBLEMS AND EXERCISES - Abduvalieva Komila Khudoiberdievna (Western European Studies, 2024)
This article presents methodological recommendations and examples for utilizing the Programmed for International Student Assessment (PISA) methodology in evaluating students' knowledge while they solve chemical problems. It also provides insights into the application of PISA research in teaching chemistry in general education schools, focusing on the development of competencies related to science and practical applications in everyday life.
Keywords: Chemical education; PISA research; competence